THE DIFFERENCES BETWEEN INTROVERT AND EXTROVERT STUDENTS ON THEIR SPEAKING PERFORMENCE - Wahyuni, Kiki; Sofia, Nur Zarit; Fadhillah, Murni; Ihsan, Muhammad Taufik (AUFKLARUNG: Jurnal Kajian Bahasa, Sastra Indonesia, dan Pembelajarannya, 2022)
The aims of this study was to find out how the difference in speaking skills between introverted and extroverted students in English class. This can be seen from class activities, speaking materials to strategies that have been applied in several studies. This article is in the form of a document and a literature review, on the basis of a knowledge evaluation. To conclude, there are some significant differences in speaking performace between extroverted and introverted students. The results of the study showed that extroverted students were superior to introverted students in speaking performance. And teachers or lecturers can also try to accommodate and facilitate students based on their preferred learning style